The road to character - Brooks, David, 1961- (New York : Random House, 2015)
"#1 New York Times bestselling author David Brooks, a controversial and eye-opening look at how our culture has lost sight of the value of humility - defined as the opposite of self-preoccupation - and why only an engaged inner life can yield true meaning and fulfillment"--
Includes bibliographical references (pages 275-284) and index.
Keywords: Philosophy -- Ethics & Moral Philosophy